PENDEKATAN PEMBELAJARAN MEMBACA PADA BUKU TEKS PELAJARAN TEMATIK KELAS III SD/MI DI KECAMATAN PURBALINGGA - Dedy Irawan; Cicih Wiarsih; Asih Ernwati (Khazanah Pendidikan, 2021)
Text book used at Indonesian elementary school particularly the reading sections play significant role for 1st – 3rd grade students as it prepares them to master their reading skill at 4th – 6th grade. Reading strategies which appropriate to students needs should be implemented to give rooms for student to exercise their reading skills. Occurred from April to June 2021, this study aimed to determine whether or not the five text books used at Purbalingga regency  are suitable for students, and to find out what kind of reading strategy used in those textbooks. As a library research, the prime source of this study is five textbooks for 3rd grade students from which Miles and Huberman model was used to analyzed the data. The findings showed that the five textbooks are all suitable, they fitted the criteria to be categorized as good and proper for teaching reading. Three out of the five textbooks utilized whole language reading strategy, the other two textbooks, brought into play both contextual and whole language reading strategies. These two reading strategies encourage students to be active participants and all the five textbooks make this possible through various independent reading activities.